APE2 promotes DNA damage response pathway from a single-strand break. Issue 5 (19th January 2018) - Lin, Yunfeng; Bai, Liping; Cupello, Steven; Hossain, Md Akram; Deem, Bradley; McLeod, Melissa; Raj, Jude; Yan, Shan
Abstract: As the most common type of DNA damage, DNA single-strand breaks (SSBs) are primarily repaired by the SSB repair mechanism. If not repaired properly or promptly, unrepaired SSBs lead to genome stability and have been implicated in cancer and neurodegenerative diseases. However, it remains unknown how unrepaired SSBs are recognized by DNA damage response (DDR) pathway, largely because of the lack of a feasible experimental system. Here, we demonstrate evidence showing that an ATR-dependent checkpoint signaling is activated by a defined plasmid-based site-specific SSB structure in Xenopus HSS (high-speed supernatant) system. Notably, the distinct SSB signaling requires APE2 and canonical checkpoint proteins, including ATR, ATRIP, TopBP1, Rad9 and Claspin. Importantly, the SSB-induced ATR DDR is essential for SSB repair. We and others show that APE2 interacts with PCNA via its PIP box and preferentially interacts with ssDNA via its C-terminus Zf–GRF domain, a conserved motif found in >100 proteins involved in DNA/RNA metabolism. Here, we identify a novel mode of APE2–PCNA interaction via APE2 Zf–GRF and PCNA C-terminus. Mechanistically, the APE2 Zf–GRF–PCNA interaction facilitates 3′-5′ SSB end resection, checkpoint protein complex assembly, and SSB-induced DDR pathway. Together, we propose that APE2 promotes ATR–Chk1 DDR pathway from a single-strand break.